Myocardial perfusion magnetic resonance imaging for detecting coronary function anomalies in asymptomatic paediatric patients with a previous arterial switch operation for the transposition of great arteries - Manso, B.; Castellote, A.; Dos, L.; Casaldáliga, J. (Cardiology in the young, 2010)
The main cause of long-term morbidity and mortality after the arterial switch operation for transposition of great arteries is complication at the coronary arteries. Myocardial perfusion magnetic resonance imaging represents a relatively novel and appealing tool for detecting myocardial ischaemia but with little experience in paediatric patients. The purpose of this paper is to report a single centre experience with myocardial perfusion magnetic resonance imaging for detecting ischaemia after the arterial switch operation for transposition of great arteries. Twenty-eight patients aged 13-16 years with an arterial switch operation for transposition of great arteries were included in the study. Coronary pattern, operative and postoperative complications, and long-term follow-up events were reviewed. Patient functional evaluation included clinical examination, electrocardiogram and echocardiogram. Every patient underwent magnetic resonance imaging perfusion scanning at rest and under adenosine-induced stress. All patients were symptom free with no ischaemic signs on the electrocardiogram. All magnetic resonance imaging examinations were generally well tolerated with minor adenosine secondary effects in 36% of the patients. Two stress myocardial perfusion magnetic resonance studies were excluded from analysis for technical reasons. No perfusion stress defects were detected at the remaining 26. Myocardial delayed enhancement was performed in all 28 patients. In five subjects, a subendocardial late enhancement consistent with patch tissue for septal defect closure at the time of repair was indentified. Magnetic resonance imaging evaluation of myocardial perfusion and viability is feasible in paediatric patients long after arterial switch operation. No signs of myocardial ischaemia or necrosis were documented in this young asymptomatic population. Further studies including coronary angiography correlation are needed to validate magnetic resonance imaging results.